Penerapan Sistem Manajemen Keselamatan Dan Kesehatan Kerja Di RSUD Kota Makassar - Karlyna Bte Muhammad (The Journal General Health and Pharmaceutical Sciences Research, 2024)
The workplace is where tasks are carried out to produce goods and services. The implementation of Occupational Health and Safety (OHS) programs in a company can support the improvement of workforce productivity, thereby yielding benefits automatically. The research population consisted of 737 individuals, namely all employees registered as hospital staff, while the research sample consisted of 10 individuals who have authority in implementing the Occupational Health and Safety Management System (OHSMS) at the Hospital in Makassar City. The research was conducted using qualitative survey methods through purposive sampling. Data were collected through interviews and direct observations. The results of this research examined commitments and policies, planning, organizing, and implementing OHS at the Hospital in Makassar City. Commitments and policies from leadership regarding OHS implementation already exist and are documented, but they have not been effectively socialized to all elements in the hospital. OHS planning at the Hospital in Makassar City has been conducted before program formulation, including data collection and priority setting. Organizing is done by forming the PK3RS organization. OHS implementation is carried out in the form of training, socialization, and provision of personal protective equipment, but still in very minimal quantities. Evaluation and review have not been carried out because the implementation of OHS at the Hospital in Makassar City has only been running for about 6 months. Recommendations for management include strengthening commitments to improve PK3RS performance, ensuring the provision of qualified PK3RS personnel, and communicating OHS to all levels of management, employees, patients, and hospital visitors.